(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article deals with the problems of translation and terminology in Kyrgyz linguistics. It is noted that terminology is a special field of linguistics, and terms – a special subsystem of the lexical base of the language that constantly changes and replenishes. At the same time, the idea is expressed that the terms undergo a continuous process of renewal and expansionWe know that on innovations, discoveries and successes created in the natural sciences, meetings are held and discussed by a special international commission in order to systematize the names of the corresponding concepts and accepted units. In the context of the rapid development of science and technology, terminology needs to be updated. Thus, the issue of its formation and renewal should always be purposeful. No branch of science should allow the chaotic development of its terminology. The article expresses the opinions on the principles of formation and development of terminology.